The effects of corpus-based collocation approach using Pakistani English online newspapers on creative writing among secondary level EFL Pakistani learners - Akhter, Shamim (2024)
Research on the usage of lexical collocation to improve creative writing is considerably lacking in Pakistan, as researchers have been focusing on examining the impact of collocation on reading, speaking, and listening. Furthermore, it was observed that students at the secondary level faced difficulties in English writing. Their writing lacked adequate combinations of words according to the context. The present study intended to explore the effects of corpus-based collocation approach on creative writing among the EFL learners at the secondary level in Punjab, Pakistan. The research participants comprised 60 secondary- level students and pre-test and post-test were administrated to collect data quantitatively, and a paired samples T-test was applied to analyse the data statistically. The qualitative data were collected through semi-structured interviews and a thematic analysis was used to examine the themes in the responses of the students. The results of the study revealed that the participants of the two groups possessed inadequate collocation knowledge. The corpus-based collocation intervention was found to be strongly and significantly effective and assisted the students in the experimental group to enhance their collocation knowledge and creative writing. This study implies that collocation knowledge plays a significant role in enhancing EFL secondary learners’ creative writing.